Study on force characteristics in accordance with gear ratio of the linear magnetic gear - Won Seo, Sung; Hun Shin, Kyung; Hong, Keyyong; Hwan Kim, Kyong; Young Choi, Jang (International Journal of Engineering and Technology, 2018)
We have studied linear magnetic gears. Since linear magnetic gears are excellent in terms of ease of manufacture and economy, we studied linear magnetic gears in this paper. The speed and the force of the secondary side of the magnetic gear are determined according to the gear ratio. In additional, the linear magnetic gear also performs a linear reciprocating motion different from the rotary magnetic gear. Therefore, in this paper, the model selection was made through reference works. The selected models had analyzed in accordance with gear ratio.Especially, the characteristics analysis method was compared with total harmonic distortion and force ripple. Also, it is possible to predict and compare the total harmonic distortion, the force ripple, and the speed according to the gear ratio. Finally, the speed comparison between the primary side and the secondary side of the gear ratio was carried out and the validity of the research direction of the linear gear was verified through all the results. All results are important for predicting gear ratio selection of precision linear magnetic gears. Therefore, in this paper, the load force is set opposite to the secondary side, and through this process to obtain accurate results from the analysis of the linear magnetic gear. From the analysis results of this paper, we can analyze the combined model of linear magnetic gear and linear generator.Â